Clinical and Haemato-Biochemical Studies of Ruminal Acidosis in Goats of Rajendranagar Mandal of Hyderabad - TAMBE SATISH VALMIK; DR. K. PADMAJA (International Journal of Pharma and Bio Sciences, 2018)
The present study was carried out on thirty goats that were presented with the history of dietary abnormalities, excessive ingestion of carbohydrate-rich diet viz., wheat and wheat flour, roti, chapatti, boiled rice, vegetables like potatoes, banana and ceremonial wastes, and which were subjected to poor management, reared under semi-intensive system as well as left for free grazing at peri-urban area. The goats which showed in appetence, anorexia, suspended rumination and clinical manifestations of distended rumen and diarrhoea were selected. Clinical signs, haematological, biochemical and urine analysis were undertaken on affected goats and compared against ten apparently healthy goats (Group IV) from the same area with similar husbandry practices which served as healthy control group. Based on severity of clinical signs and clinical observation such as ruminal fluid pH, these goats were grouped into three different groups as mild acidosis (pH=5.5- 6.5), moderate acidosis (pH=4.5-5.5), and severe acidosis (pH=4.0-4.5) group I, II and III respectively, consisting of 10 goats in each. Ruminal acidotic goats had significant increase in clinical parameters such as heart and respiration rates and skin-fold time; haematological parameters such as haemoglobin, packed cell volume, total leucocyte count, neutrophils, eosinophils, and monocytes. But there was a significant decrease in body temperature, rumen motility, urine pH and blood lymphocytes. Colour of conjunctival mucous membrane was normal, slightly congested and congested in group I, II and III respectively. Urine was positive for Benedict’s test in all acidotic goats as compared to group IV. It was concluded that, there was a significantly altered clinical, haemato-biochemical and urine parameters in all acidotic goats when compared with healthy goats.